(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to identify the impact of artificial intelligence on the strategic decision-making process in multinational companies. The study used the descriptive analysis method and collected data using a random sample. The study sample consisted of 456 individuals. The research reached a number of results, one of which is that a large number of multinational companies in Saudi Arabia use computers equipped with artificial intelligence, and it has been proven that these institutions are capable of making strategic decisions. In addition, a high level of application of intelligent agents, artificial neural networks, and expert systems has been proven. In addition, intelligent agents, expert systems, artificial neural networks, and artificial intelligence have all been shown to have a significant impact on the process by which multinational companies make their strategic decisions. The study concluded that enabling multinational companies in Saudi Arabia to fully benefit from artificial intelligence requires creating the appropriate environment for its application and providing the necessary technological infrastructure. The study also emphasized the importance of employing individuals with extensive scientific and practical knowledge of artificial intelligence, and sought to provide Saudi employees with training programs and courses to maximize their potential in dealing with artificial intelligence and related technologies.